Stresses at weld toes in tubular joints in offshore structures - Elliott, Kim S. (1987)
The accurate prediction of stress concentration factors (SCF) at weld toes is recognised as one of the most important factors in the design, against fatigue failure, of welded tubular joints in offshore structures. The objectives of this work are i) to study the influence of some important tubular joint and weld profile geometric parameters on the elastic SCFs at weld toes, ii) compare these values with strains which could be measured by strain gauges, and iii) to determine plastic-elastic strain distributions after local yielding has occurred in the weld. Using 3-d frozen-stress, photoelastic techniques elastic SCFs were determined in non-overlapped corner K joints in balanced axial loading and in X joints in axial loading. For typical tube parameters, results have been obtained for different brace angles, brace spacings, weld size, weld angle and weld toe radii in the crown and saddle planes at the brace and chord wall ends of the weld. They have been presented as the product of a shell SCF Ks and a notch SCF Kn . Ks, which was measured at the weld toe, depends on position in the brace intersection, brace angle, brace spacing and weld size. Kn depends on weld toe radius, weld angle and weld size. Large scale 2-d photoelastic and finite element models were used to study the influence of weld profile "qualities" on Ks and Kn. Weld shapes conforming with minimum profiling requirements are called "uncontrolled". Improved weld shapes wi th concave profiles are called "controlled". The reductions in SCFs, due to the different profiles, depend on position (crown or saddle) when the results are presented for identical weld geometry. Plastic-elastic and residual plastic strains were obtained in 2-d steel weldments using reflection photoelasticity and moire interferometry experimental techniques. A moire interferometer, using Helium-Neon laser light and high sensitivity diffraction gratings was designed and built for this purpose. Strains were measured in the range 20µε to 2%. Strain concentration factors of between 13 and 17 were determined in models in which the corresponding elastic values were 3.6 and 4.6 respectively.